Ferroptosis in liver cancer: a key role of post-translational modifications - Xu, Ying; Xing, Zhiyao; Abdalla Ibrahim Suliman, Ruaa; Liu, Zichuan; Tang, Fengyuan (Frontiers in Immunology, 2024)
Ferroptosis is an emerging form of regulated cell death in an oxidative stress- and iron-dependent manner, primarily induced by the over-production of reactive oxygen species (ROS). Manipulation of ferroptosis has been considered a promising therapeutic approach to inhibit liver tumor growth. Nevertheless, the development of resistance to ferroptosis in liver cancer poses a significant challenge in cancer treatment. Post-translational modifications (PTMs) are crucial enzymatic catalytic reactions that covalently regulate protein conformation, stability and cellular activities. Additionally, PTMs play pivotal roles in various biological processes and divergent programmed cell death, including ferroptosis. Importantly, key PTMs regulators involved in ferroptosis have been identified as potential targets for cancer therapy. PTMs function of two proteins, SLC7A11, GPX4 involved in ferroptosis resistance have been extensively investigated in recent years. This review will summarize the roles of PTMs in ferroptosis-related proteins in hepatocellular carcinoma (HCC) treatment.